Using GIS to Understand Cervical Cancer Screening Behaviors among Women Living with HIV (WLWH) in Ghana - Barimah Owusu, Alex; Asare, Matthew; Owusu, Ruth (Asian Pacific Journal of Environment and Cancer, 2022)
Objective: This study used the Geographic Intelligent Systems to examine the location of cervical cancer screening (CCS) facilities and their proximity to the residential location of Women Living with HIV (WLWH) and how they could influence WLWH CCS behaviors. Methods: We used deidentified existing data from Komfo Anokye Teaching Hospital (KATH) on WLWH and geocoded them to their community of residence as points using Google Earth Pro version 7.3.0. Transport fares from KATH to communities identified in the screening database were also obtained. The location of KATH was digitized from google earth and validated from the GIS database from the Remote Sensing and GIS application Laboratory, University of Ghana. We calculated distances and other proximity information between each point from the KATH. We used the spatial-analytical tool of kernel density for the density analysis and fitted a smoothly tapered surface using Esri’s ArcGIS Desktop 10.8. We performed Shapiro-Wilk normal distribution test to assess the significance of the clustering. Results: Data on 708 WLWH’s residential locations and transportation fares were analyzed. We find a significant clustering near KATH. Close to 50% cluster within 5km from KATH whiles 85.8% of the respondents live within 10.2 km from KATH. Shapiro-Wilk normality test shows W=0.30221, p-value < 0.05. The minimum cost per commercial transportation is approximately GHC 2.00 (US dollar ~ $0.26 whiles those living beyond 3-5 km will pay approximately GHC 3.00 (~$0.39). The highest cost payable by the farthest distance using a commercial bus is GHC 50.00. (~$ 6.00). The majority of respondents will pay about GHC 10.00 (~$1.50) for transportation (i.e., round trip) to access SCC facilities. Conclusions: In an economy where a family lives on less than $2.00 per day, any additional cost resulting from transportation will likely create CCS hesitancy and that self-sampling may be a recommended solution.